2022
DOI: 10.1021/acsnano.2c08543
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive Nanomaterials for Wireless Neural Biomimetics, Stimulation, and Regeneration

Abstract: Nanomaterials at the neural interface can provide the bridge between bioelectronic devices and native neural tissues and achieve bidirectional transmission of signals with our brain. Photoactive nanomaterials, such as inorganic and polymeric nanoparticles, nanotubes, nanowires, nanorods, nanosheets or related, are being explored to mimic, modulate, control, or even substitute the functions of neural cells or tissues. They show great promise in next generation technologies for the neural interface with excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 127 publications
(247 reference statements)
0
8
0
Order By: Relevance
“…The effects of light stimulation have been published on cells adhered to various photoelectric materials. , Most previous studies used a single material, only examined cellular responses to one level of stimulation, and only reported the favorable effects of light exposure on cells. ,,, By applying different surface treatments to N-UNCD, we were able to examine the cellular response to varying magnitudes of the photocurrent and their mechanisms. We generally observed that the 15-h OA N-UNCD sample produced the most beneficial effect on cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of light stimulation have been published on cells adhered to various photoelectric materials. , Most previous studies used a single material, only examined cellular responses to one level of stimulation, and only reported the favorable effects of light exposure on cells. ,,, By applying different surface treatments to N-UNCD, we were able to examine the cellular response to varying magnitudes of the photocurrent and their mechanisms. We generally observed that the 15-h OA N-UNCD sample produced the most beneficial effect on cells.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 A range of photoelectric materials have been developed and employed to modulate neural activities by converting light into electrical signals. 2,5 Compared to direct electrical stimulation, optical stimulation via these photoelectric materials provides several advantages. 6 First, optical stimulation eliminates the need for wires that connect electronic implants with external devices for powering and data transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Materials with optical properties have shown potential for converting light into various forms of stimuli to modulate biological processes or biomolecular activities. [192][193][194] Among these materials, photoelectric materials that generate electric current upon light illumination are crucial for neural modulation, providing new opportunities for remote and wireless electrical stimulation (Fig. 5A).…”
Section: Functional Material-mediated Wireless Physical Signals For N...mentioning
confidence: 99%
“…[1][2][3] These stimuli all target neuromodulationrelated biological entities such as mechanically activated, voltage-gated, light-gated and thermosensitive ion channels. 4,5 To date, mechanical and electrical stimuli have been extensively studied by designing smart stimulus-responsive scaffolds, while light and thermal modalities have been relatively unexplored. Although with advantages and flexibility due to easy operability, light stimulus is usually combined with an optogenetics tool to modulate neuro-behavior, thus restricting it to the poor tissue penetration of the visible light operator, complex processes and high process costs.…”
Section: Introductionmentioning
confidence: 99%